KOORDINASI KOMISI PENANGGULANGAN AIDS (KPA) KOTA PEKANBARU DENGAN LEMBAGA SWADAYA MASYARAKAT (LSM) DALAM UPAYA PENANGGULANGAN HIV/AIDS DI PEKANBARU - Tambunan, Andreas Maruli Tua; Tua RFS, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The cases of HIV and AIDS increase every year. These cause the importance of the role of KPA and LSM in HIV / AIDS prevention efforts. One of the efforts is the good coordination between KPA and LSM. The purpose of the coordination is to reduce the rate of cases of HIV and AIDS.The purpose of this research is to analyze the act of the coordination between KPA Pekanbaru with LSM, and also the facts that influence coordination in HIV / AIDS prevention efforts in Pekanbaru. This research uses the concept of coordination theory by Henry Fayol and Cyrill O?Donnell. The research is qualitative with data collection using interview method, observation and documentation.Based on the result of this research by interviewing and observation, it can be seen that the coordination between KPA Pekanbaru and LSM has been good. This is seen from the good communication and cooperation, regular meetings which are held to give reports and informations and to evaluate the performance of both. There are some facts that influence this coordination. They are facilities and infrastructures, human resources and funds. Keywords : Koordination, Prevention, HIV and AIDS